Rescue RM/CS-AKI by blocking strategy with one-dose anti-myoglobin RabMAb - Xinyue Wang; Ning Li; Lu Han; Ou Qiao; Xin Chen; Pengtao Wang; Lancao Zhang; Yingjie Hou; Fengjiao Bao; Herui Hao; Sania Saeed; Li Zhang; et al. (Nature Communications)
Abstract Rhabdomyolysis or Crush syndrome-related AKI (RM/CS-AKI) has high mortality, and there is no effective early on-site treatment method. The critical pathogenic factor of RM/CS-AKI is the excessive free myoglobin (Mb) in blood circulation. Here, based on the concept of creating a “mobile barrier”, we develop an anti-Mb rabbit monoclonal antibody (RabMAb) with high specificity, affinity, stability, and broad species reactivity. A single dose of anti-Mb RabMAb injection is sufficient for emergency rescue in both homologous and heterologous RM/CS-AKI male animal models. The main goal of blocking the passage of free Mb through the glomerular filtration barrier has been achieved by using the anti-Mb RabMAb, which has a long-term stable therapeutic effect within 14 days and promotes phagocytosis of Mb. The optimal administration strategy, pharmacokinetic analysis, toxicity evaluation for anti-Mb RabMAb, and the distribution of its immune complexes in RM/CS-AKI mice are investigated. Thus, we develop effective prevention and control strategies for RM/CS-AKI.